Analisis Efisiensi Pemasaran Produk Spa yang Laris Terjual pada PT Bali Tangi - NI KADEK WINDA YULIASARI; I GUSTI AGUNG AYU AMBARAWATI; I KETUT RANTAU (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Marketing Efficiency Analysis of Best Seller Spa Products at PT Bali Tangi This research is aimed to find out the marketing channels, to calculate marketingmargin, producer’s share, and to analyze marketing efficiency of best seller spaproducts at PT Bali Tangi. This company produces three types of spa productsnamely scrub, masker and massage oil that are in high demand. Samples wereselected purposively for retailers from PT Bali and snowball sampling for retailersfrom the wholesaler. Total samples were 30 from Denpasar City and BadungRegency including wholesaler, retailers, hotels and villas. The results showed thatthere are three types of marketing channels of best seller spa products of PT BaliTangi. Channel I: producer – end consumers (for three spa products), channel II:producer – retailers and institutional consumers – end consumers (for three spaproducts), and channel III: producer - wholesaler - institutional consumers – endconsumers (for only two spa products). The channel II comprises 52.95% of the totalsales, whereas 8.97% and 38.07% respectively for channel I and III. The highestmarketing margin was seen from the channel III at amount of Rp 80,000/unit, whileno marketing margin coming from the channel I as it is direct marketing. Thechannel II has marketing margin Rp 25,000. The highest producer’s share is onchannel I by 100% and the lowest is on channel III by 57.89%. The channel II hasproducer’share of 86.49%. In terms of marketing efficiency, this research does notcompare to channel I because channel I does not have a marketing agency. ChannelII of the marketing channel is the most efficient based on three analysis of marketingmargins, producer’s share, and price efficiency. Channel III is only efficient atoperational efficiency of 2,944.57%. Meanwhile, channel III is inefficient. Despite ofinefficiency, channel III is the main supporting channel for the company to maintaindue to high volume of trading compared to channel I.